2023
DOI: 10.5194/isprs-archives-xlviii-m-1-2023-293-2023
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for Comparing Multi-Temporal Archive Aerial Imagery for Glacier Monitoring With Poor Ground Control

Abstract: Abstract. The measurement of geometric changes in Alpine glaciers is an essential aspect to assess their reaction to climate change effects. Archive aerial images may integrate valuable information to this purpose at times when other types of remotely sensed data are not available. The application of photogrammetric techniques such as Structure-from-Motion (SfM) and Multi-View-Stereo matching allows the extraction of dense point clouds to model the glacier environment. The comparison of multiple datasets requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…In this article the focus is given to the Multitemporal Structure-from-Motion (MSfM), which is presented here as a solution to obtain an accurate coregistration between photogrammetric blocks captured at different epochs. While this approach was already presented by the authors to deal with multitemporal data sets of aerial archive photos (Scaioni et al, 2023), here the methodology is reported with the general purpose to align any type of aerial data, including the integration of different data types in the same project (see Sect. 2).…”
Section: Motivationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this article the focus is given to the Multitemporal Structure-from-Motion (MSfM), which is presented here as a solution to obtain an accurate coregistration between photogrammetric blocks captured at different epochs. While this approach was already presented by the authors to deal with multitemporal data sets of aerial archive photos (Scaioni et al, 2023), here the methodology is reported with the general purpose to align any type of aerial data, including the integration of different data types in the same project (see Sect. 2).…”
Section: Motivationsmentioning
confidence: 99%
“…The processing pipeline described in Subsection 2.2 for MSfM has been applied to the aerial blocks in Table 1. More details can be found in Scaioni et al (2023). A set of seven GCPs has been initially used for georeferencing all blocks in the reference frame RDN 2008.0 / UTM32N.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation